Circus to the south: a journey along the processes of institutionalization of the circus facing the 21st century (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This paper focused on some of the institutionalization processes the Circus Arts have been experiencing in the last decades in Uruguay. Although its presence as an artistic field is long and generally well known, it is only in the last few years that a path through which the Circus is studied, researched and systematized has been opened. This is not an isolated process but the product of this practice’s particular journey since the late 1990’. It is related, among other factors, to the consolidation of community based educational processes allied with cultural and educational policies, to its incorporation in the university environment, and the creation of nets aiming at organizing and facilitating demands from the sector, which faces state policies supporting the culture. For this particular work the case of the Circus in El Picadero and in the Instituto Superior de Educación Física de la Universidad de la República (Physical Education Superior Institute -ISEF, Udelar-) was approached.
Keywords: Circus; Uruguay; El Picadero; University